A New Stability Indicating RP-HPLC Method Development and Validation for the Simultaneous Estimation of Dolutegravir and Rilpivirine in Bulk and its Dosage Forms: Stability indicating analytical method for simultaneous estimation of Dolutegravir and Rilpivirine by RP-HPLC - Ismail, Yusuff; Vara Prasad, M.Vijaya; Shaheedha, S. M.; Habeeb, Mohammad (Iranian Journal of Pharmaceutical Sciences, 2019)
The objective of the work is to develop and validate a new, simple, highly sensitive, stability indicating RPHPLC method for simultaneous estimation of Dolutegravir and Rilpivirine in bulk and its dosage forms. The method was developed on a reversed-phase Thermosil C18 (4.6 × 150 mm, 5μm) column with an isocratic elution. The Mobile phase ratio was Acetonitrile: Phosphate Buffer pH 3.5 (45:55 % v/v). Detection was done by UV-Spectroscopy at a detection wavelength of 260 nm. The flow rate was 0.8 ml/min. The mobile phase was used as a diluent. The Injection volume was 10μl. The analytical procedure was validated as per ICH guidelines. The retention time for Dolutegravir and Rilpivirine in the standard solution having the concentration of 100 μg/ml of Dolutegravir and 50 μg/ml of Rilpivirine were observed to be around 2.427 min and 4.436 min. respectively. The purity percentage values of Dolutegravir and Rilpivirine were 99.22 % w/v and 99.81 % w/v respectively. System suitability parameters were calculated and found within the acceptance criteria. The proposed method was found to have a high degree of precision and reproducibility. Calibration plots were linear (r2> 0.999) over the concentration range of 80 - 120 μg/ml for Dolutegravir and 30 - 70 μg/ml for Rilpivirine.The recovery percent were within the acceptance criteria of 98 – 102 % for Dolutegravir and Rilpivirine. The LOD was 0.044 μg/ml for Dolutegravir and 0.060 μg/ml for Rilpivirine. The LOQ was 0.134 μg/ml for Dolutegravir and 0.183 μg/ml for Rilpivirine. The method represents a fast-analytical procedure and stability indicating analytical method for the simultaneous estimation of Dolutegravir and Rilpivirine in bulk and its dosage forms. No interference from any component of pharmaceutical dosage form was observed. Validation studies revealed that the method is specific, rapid, reliable, and reproducible. The method is amenable to the routine analysis of large numbers of samples with good precision and accuracy.